Measuring data quality for ongoing improvement : a data quality assessment framework - Sebastian-Coleman, Laura (Morgan Kaufmann, 2013)
Shows you how to measure and monitor data quality, ensuring quality over time. This title demonstrates how to leverage a technology independent data quality measurement framework for specific business priorities and data quality challenges. It enables discussions between business and IT with a non-technical vocabulary for data quality measurement